Zamfirescu mappings under Pata-type condition: results and application to an integral equation - Chand, Deep; Rohen, Yumnam; Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Pata-type and Zamfirescu mappings are extended beyond metric spaces.Methods: The concept of Pata-type Zamfirescu mapping within the framework of S-metric spaces is employed.Results: A series of corresponding outcomes has been established. Furthermore, the obtained results are employed to solve an integral equation.Conclusions: S-Pata type and Zamfirescu mappings have unique fixed points.
Keywords: Pata-type contraction; Zamfirescu mapping; S-Metric space; fixed point